A Deconstructive Analysis Of The Short Story “Saleema” By Daniyal Mueenuddin - Omama Tanvir (University of Chitral Journal of Linguistics and Literature, 2025)
The aim of this research is to apply deconstructive approach to a short story. For this purpose Daniyal Mueenuddin’s short story “Saleema” is selected and analyzed. Through deconstruction the feminist reading of the story is dismantled and the power dynamics of the patriarchal Pakistani society are subverted. The research is anchored in Derrida’s concept of unreliability of language and Cuddon’s idea of reversal of binary oppositions. The paper finds that the protagonist Saleema is not as weak and oppressed as she is perceived to be, rather she is a resilient, independent woman who uses any means possible to get what she wants. The power and authority reside with her and not with any male character. The study is purely qualitative and exploratory in nature.